A modular transformerless DC-DC step-up converter with very high voltage gain and adjustable switch stress. Issue 2 (3rd April 2018) - Salimi, Mahdi; Pornadem, Maryam
Abstract: According to limited voltage gain of the standard step-up converters, cascade connection of the boost choppers can be employed to increase voltage gain. However, negative impedance instability problem due to converters constant power characteristic will complicate closed loop control of the cascaded converters. To cope with the problem, switched capacitor/switched inductor (SC/SI) circuits can be employed for voltage gain increment in transformerless DC–DC converters. High gain DC–DC converter model includes several state variables; hence multiple voltage and current sensors are required in closed loop applications. In this paper, a novel transformerless DC–DC step-up converter with very high voltage gain is proposed using SC/SI circuits which mitigates negative impedance instability problem. By modular extension, more improvements in converter gain and switch voltage stress can be obtained. In the developed circuit, inductors currents (and voltages of the capacitors) are equal during transient and steady-state conditions. Thus, model complexity is similar to standard DC–DC converters. Experimental response of the designed system is investigated in both continuous and discontinuous conduction modes of operation. Considering different performance parameters, proposed DC–DC converter is compared with recently reported methods. Closed loop response of the presented regulator is studied using two-loop control strategy under load and line changes.